Development of Gastroretentive Microspheres for Depression Using Venlafaxine and Metformin - Sen, Jyoti; Malik, Jitender Kumar; Singh, Surendra Pratap; Jhariya, Deepak; Arya, Sunita (Journal of Neonatal Surgery, 2025)
Depression affects millions globally, requiring effective therapeutic interventions with sustained drug delivery systems. This study aimed to develop gastroretentive microspheres containing venlafaxine and metformin for enhanced treatment of depression. The objective was to formulate microspheres that provide controlled drug release, improved bioavailability, and reduced dosing frequency. The methodology involved emulsification phase separation technique using natural polymers including chitosan and alginate. Microspheres were characterized for particle size, drug loading, entrapment efficiency, and in vitro drug release. The hypothesis proposed that dual-drug gastroretentive microspheres would demonstrate superior therapeutic efficacy compared to conventional formulations. Results indicated optimal microsphere formation with 78.5% drug entrapment efficiency and sustained drug release over 12 hours. The mean particle size was 145.2 μm with excellent floating properties lasting 8 hours. Drug release followed Korsmeyer-Peppas model indicating non-Fickian diffusion mechanism. The combination showed synergistic effects with venlafaxine providing antidepressant action while metformin contributed to metabolic regulation. Statistical analysis revealed significant improvement in dissolution parameters (p<0.05). The gastroretentive microspheres demonstrated enhanced gastric residence time, controlled drug release, and improved therapeutic outcomes. This innovative formulation offers promising potential for depression management with reduced side effects and improved patient compliance through sustained drug delivery system